Estudo das propriedades físico-químicas de filmes de amido e blendas amido/látex: propriedades térmicas e de transporte de vapor de água - Heliodoro, Vanessa Freitas Mateus (2013)
In this work, films of starch and blends of starch/natural rubber latex were produced and characterized by physicochemical properties and evaluation of the water Vapor Permeation. The characterization techniques used were Fourier Transformed Infrared spectroscopy (FTIR), X-Ray Diffraction (XRD), Differential Scanning Calorimetry (DSC) and Scanning Electron Microscopy (SEM). The spectra in the infrared region of the blends showed changes in the profile and displacement of the absorption bands near 3500 cm-1 when compared to starch films. These modifications are related to changes in the pattern of hydrogen bonds with the addition of latex and glycerol in blends with plasticizer due to the mixing process. These changes are more significant for the blends starch/Latex 50/50% (m/m) (A50/L50) and starch/latex /glycerol 50/48/2 (m/m) (A50/L48/G2). The water permeation results showed a reduction in permeation of the blends and this amount was reduced by about 50% in the blend A50/L50 aspect expected since the blends are more hydrophobic by inserting natural rubber. The application of Parallel Model for immiscible blends for prediction water permeability was best suited to the system since the experimental values were close to the theoretical values, especially for the blends with glycerol. The blends prepared without glycerol present deviations that are associated with the formation of porous structures resulting from the mixing process and possible phase segregation, which facilitate the transport of water by the blend. This was confirmed from the evaluation of the SEM. The micrographs showed phase separation for films with a high percentage of latex. For higher starch content, the blends are more uniform. The DRX and DSC results show that starch undergoes changes in the mixture with latex due to the presence of hydrophilic components. The natural rubber, in other hand, maintain the same value of glass transition temperature, Tg, this aspect indicates low interaction of this polymer with starch and other components of the blend. However, the addition of natural rubber leads to an increased thermal stability and reduced water absorption. The results showed that the A50/L50 blend with and without glycerol, displays the desired physical properties and is therefore compatible. Thus, the blend in question is the starting point for improving the performance of these systems.